Solid-state fermentation of Apocynum venetum L. by Aspergillus niger: Effect on phenolic compounds, antioxidant activities and metabolic syndrome-associated enzymes - Cao, Cha; Lin, Dengfan; Zhou, Yingjun; Li, Na; Wang, Yiwen; Gong, Wenbeng; Zhu, Zuohua; Liu, Chengwei; Yan, Li; Hu, Zhenxiu; Peng, Yuande; Xie, Chunliang (Frontiers in Nutrition, 2023)
This study aimed to evaluate the effect of solid-state fermentation (SSF) with Aspergillus niger on the total phenolic content (TPC), the total flavonoid content (TFC), individual phenolic contents, and antioxidant and inhibitory activities against metabolic syndrome-associated enzymes in an ethanol extract from Apocynum venetum L. (AVL). TPC, TFC, and the contents of quercetin and kaempferol during SSF were 1.52-, 1.33-, 3.64-, and 2.22-fold higher than those of native AVL in the ethyl acetate (EA) subfraction of the ethanol extract. The ABTS·+, DPPH· scavenging, and inhibitory activities against α-glucosidase and pancreatic lipase were found to be highest in the EA subfraction. Fermentation significantly increased the ABTS radical cation, DPPH radical scavenging, and pancreatic lipase inhibitory activities by 1.33, 1.39, and 1.28 times, respectively. TPC showed a significantly positive correlation with antioxidant activities or inhibition against metabolic syndrome-associated enzymes. This study provides a theoretical basis for producing tea products with enhanced antioxidant, antidiabetic, and antihyperlipidemic activities.